2008
DOI: 10.1175/bams-89-1-39
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Radar Data Assimilation in KMA's Operational Forecasting

Abstract: mode at KMA has been very smooth and successful. With great efforts from all parties, KMA is running the advanced system operationally and benefiting Korea. The WRF 3D-Var Doppler radar data-assimilation system now resides in both NCAR and KMA and serves as a very useful tool for research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Recent studies have shown that assimilation of radar data can improve the short-term forecasts of convective systems by incorporating the initial conditions of mesoscale storm structures (Weygandt et al, 2002;Sun, 2005;Dawson and Xue, 2006;Hu et al, 2006;Zhao et al, 2006;Xiao et al, 2007Xiao et al, , 2008Pu et al, 2009;Li and John, 2010;Kawabata et al, 2011). In particular, both the four-dimensional variational (4DVar) data assimilation method (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that assimilation of radar data can improve the short-term forecasts of convective systems by incorporating the initial conditions of mesoscale storm structures (Weygandt et al, 2002;Sun, 2005;Dawson and Xue, 2006;Hu et al, 2006;Zhao et al, 2006;Xiao et al, 2007Xiao et al, , 2008Pu et al, 2009;Li and John, 2010;Kawabata et al, 2011). In particular, both the four-dimensional variational (4DVar) data assimilation method (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They found a positive impact, mainly on the first 3-h of forecasting. Xiao et al (2008) verified the benefit of Doppler radar data assimilation on operational forecasting for the Korean Meteorological Administration (KMA). Zhao et al (2006) developed a three-and-half-dimensional variational data assimilation (3.5D-VAR) system for radar wind data to initialize the Navy's Coupled Ocean-Atmosphere Mesoscale Prediction System (COAMPS) model.…”
Section: Introductionmentioning
confidence: 75%
“…However, it possesses a number of advantages over 3D-Var including the ability to: a) use observations at the exact times that they are observed, which suits most asynoptic data; b) implicitly use flow-dependent background errors, which ensures the analysis quality for fast developing weather systems; and c) use a forecast model as a constraint, which enhances the dynamic balance of the final analysis. Almost all observations can be assimilated into WRF 3/4D-Var analysis, including the observations from GTS data stream, satellite (Liu & Barker, 2006) and Doppler radar (Xiao et al, 2005;2007;Xiao et al, 2008b). Recently, Liu et al (2008;2009) …”
Section: Wrf Variational (Wrf-var) Data Assimilationmentioning
confidence: 99%